2021
DOI: 10.1136/gutjnl-2020-323979
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of nucleot(s)ide analogue therapy in HBeAg-negative chronic hepatitis B: a meta-analysis

Abstract: Background and aimsSustained virological suppression and hepatitis B surface antigen (HBsAg) loss have been described after nucleot(s)ide analogue (NA) discontinuation for patients with hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB). We performed a meta-analysis of the clinical outcomes after NA discontinuation for HBeAg-negative CHB.MethodsStudies involving NA cessation in HBeAg-negative CHB individuals with a median follow-up of ≥12 months were included. Participants were HBeAg-negative at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…After the pivotal report of a high HBsAg loss rate by Hadziyannis et al, 19 several small European studies and large Asian studies have confirmed that HBsAg loss rate is increasing after cessation of Nuc in HBV suppressed patients, especially in Caucasian patients and studies with off-Nuc follow-up >4 years. 23 In particular, a randomized control trial in 21 versus 21 patients showed a 3-year off-TDF HBsAg loss rate of 19% versus 0% (p = 0.022) in those who continued TDF therapy, 24 and a large study involving 691 ETV/TDF-treated patients showed a 6-year off-Nuc HBsAg loss rate of 36% in those with sustained HBV DNA <2,000 IU/ml and 19% in un-retreated clinical relapsers. 25 It was documented that the increase in the incidence of HBsAg loss became more evident after 4-year off-Nuc therapy and was higher in Caucasian than Asian patients.…”
Section: High Hbsag Loss Rate Justifies Finite Nuc Therapy As An " Ac...mentioning
confidence: 99%
See 2 more Smart Citations
“…After the pivotal report of a high HBsAg loss rate by Hadziyannis et al, 19 several small European studies and large Asian studies have confirmed that HBsAg loss rate is increasing after cessation of Nuc in HBV suppressed patients, especially in Caucasian patients and studies with off-Nuc follow-up >4 years. 23 In particular, a randomized control trial in 21 versus 21 patients showed a 3-year off-TDF HBsAg loss rate of 19% versus 0% (p = 0.022) in those who continued TDF therapy, 24 and a large study involving 691 ETV/TDF-treated patients showed a 6-year off-Nuc HBsAg loss rate of 36% in those with sustained HBV DNA <2,000 IU/ml and 19% in un-retreated clinical relapsers. 25 It was documented that the increase in the incidence of HBsAg loss became more evident after 4-year off-Nuc therapy and was higher in Caucasian than Asian patients.…”
Section: High Hbsag Loss Rate Justifies Finite Nuc Therapy As An " Ac...mentioning
confidence: 99%
“…25 It was documented that the increase in the incidence of HBsAg loss became more evident after 4-year off-Nuc therapy and was higher in Caucasian than Asian patients. 23 The much increased incidences of HBsAg loss in Asian patients with HBeAg-negative patients off-Nuc therapy as compared with those on indefinite longterm Nuc therapy are shown in Table 1. [25][26][27][28][29][30][31] It has been proposed that immune restoration during Nuc therapy and/or HBV reactivation elicited immune response may facilitate further HBsAg decline toward HBsAg loss.…”
Section: High Hbsag Loss Rate Justifies Finite Nuc Therapy As An " Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…When HBV DNA is not detectable over a long term, and virological response is well maintained, the HBsAg loss rate increases even after cessation of therapy in patients with HBeAg-negative CHB. Therefore, cessation of therapy could be considered in these patients with long-term undetectable HBV DNA [ 244 - 246 , 250 ]. The lower is the HBV DNA level, the better is the clinical status; however, when the HBV DNA level is 60–2,000 IU/mL, the risk of cirrhosis and HCC is similar to that of patients with undetectable HBV DNA [ 68 , 70 ].…”
Section: Cessation Of Treatment and Monitoring After Antiviral Treatmentmentioning
confidence: 99%
“…Evidence for HBV DNA level as a surrogate indicator in these patients is lacking. Also, in practice, most patients with undetectable HBV DNA relapsed after cessation of NA therapy [ 194 , 244 - 246 ]. Hence, undetectable HBV DNA cannot be the sole indicator determining treatment cessation.…”
Section: Cessation Of Treatment and Monitoring After Antiviral Treatmentmentioning
confidence: 99%